2019
DOI: 10.1017/s0022377819000680
|View full text |Cite
|
Sign up to set email alerts
|

Stellarator equilibria with reactor relevant energetic particle losses

Abstract: Stellarator configurations with reactor relevant energetic particle losses are constructed by simultaneously optimizing for quasisymmetry and an analytically derived metric ( $\unicode[STIX]{x1D6E4}_{c}$ ), which attempts to align contours of the second adiabatic invariant, $J_{\Vert }$ with magnetic surfaces. Results show that with this optimization scheme it is possible to generate quasihelically symmetric equilibria on the scale of ARIES-CS which complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(115 citation statements)
references
References 38 publications
4
111
0
Order By: Relevance
“…It has, however, some disadvantage if the starting surface is close to a low-order rational surface such that one needs a very long field line to cover it. In that case, the method of Bader et al (2019) for flux coordinate systems would be preferable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, some disadvantage if the starting surface is close to a low-order rational surface such that one needs a very long field line to cover it. In that case, the method of Bader et al (2019) for flux coordinate systems would be preferable.…”
Section: Resultsmentioning
confidence: 99%
“…Direct computation of such losses with usual numerical methods is relatively time consuming compared to other calculations within the optimization loop, in particular computation of three-dimensional (3-D) magnetohydrodynamic equilibria. This is why 2 C. G. Albert, S. V. Kasilov and W. Kernbichler fusion alpha loss estimation is often performed via faster proxy models (Nemov et al 2005(Nemov et al , 2008Bader et al 2019) that, however, cannot capture the full physics of drift orbits and, therefore, are suited only for the initial stage of optimization. The reason for this is the high alpha energy of 3.5 MeV, leading to the following consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, this metric seeks to align contours of the second adiabatic invariant J with flux surfaces. Its viability in producing configurations with excellent energetic ion confinement was demonstrated in Bader et al (2019). (iii) A magnetic well (Greene 1997), where present, provides stability against interchange modes.…”
Section: Optimizationmentioning
confidence: 99%
“…In both cases, 5000 particles are included in the evaluation for each flux surface for 200 ms, which corresponds to 2 alpha slowing down times at the core ARIES-CS density (n e = 5 × 10 20 m −3 ) and temperature (T e = 12 keV) and to 10 alpha slowing down times at the mid-radius density (n e = 5 × 10 20 m −3 ) and temperature (T e = 4 keV). Previous calculations indicated that 5000 particles per flux surface were sufficient for Monte Carlo statistical purposes (Bader et al 2019). These calculations only consider the vacuum fields, and improvements with finite pressure and plasma currents are left for future optimization studies.…”
Section: Energetic Particlesmentioning
confidence: 99%
See 1 more Smart Citation